Biowaste Management: Comparison of Banana (Musa acuminata) and Bamboo (Bambusa vulgaris) Fibers - Dhesighraja Jeyaraj; Mayandi Kalimuthu; Rajini Nagarajan; Prakash Chithamparam; Sikiru O. Ismail; Faruq Mohammad; Hamad A. Al-Lohedan; Kumar Krishnan (BioResources, 2024)
Both developed and developing countries around the world are increasingly utilizing biodegradable products and bio-based materials. This is required to curb rampant environmental pollution caused by synthetic materials and their by-products. In this study, banana and bamboo fibers were prepared from agricultural and industrial wastes, respectively. Banana and bamboo fibers were obtained with aid of mechanical and waste extractions, respectively. Both fibers were subjected to a retting process for 24 hours, using normal warm water at a room temperature (27 ± 3 °C) to remove the impurities. Then, a comparative investigation and analysis was conducted concerning their properties and applications. The biomass level, physical, and chemical properties, structure, experimental analysis, and moisture regain behaviors of the plant materials were studied. Additionally, the antibacterial property of the samples was discussed. The biomass level was measured per hectare for banana (36.1 tons) and per plant for bamboo (65%), and the physical and chemical properties were identified via some basic testing techniques. The molecular, crystalline, and morphology structures were observed using Fourier-transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. Finally, the industrial applications were elucidated to establish the possibility of using both fibers as promising sustainable, renewable, recyclable, and eco-friendly materials.